Principles of Neural Repair and Their Application to Stroke Recovery Trials - Lin, David J.; Cramer, Steven C. (Seminars in Neurology, 2021)
Neural repair is the underlying therapeutic strategy for many treatments currently under investigation to improve recovery after stroke. Repair-based therapies are distinct from acute stroke strategies: instead of salvaging threatened brain tissue, the goal is to improve behavioral outcomes on the basis of experience-dependent brain plasticity. Furthermore, timing, concomitant behavioral experiences, modality specific outcome measures, and careful patient selection are fundamental concepts for stroke recovery trials that can be deduced from principles of neural repair. Here we discuss core principles of neural repair and their implications for stroke recovery trials, highlighting related issues from key studies in humans. Research suggests a future in which neural repair therapies are personalized based on measures of brain structure and function, genetics, and lifestyle factors.
Keywords: stroke; recovery; rehabilitation; clinical trials; plasticity